2017
DOI: 10.1037/sgd0000218
|View full text |Cite
|
Sign up to set email alerts
|

Development of gender identity implicit association tests to assess attitudes toward transmen and transwomen.

Abstract: The purpose of this study was to develop and validate 2 gender identity implicit association tests (GI-IATs) designed to assess attitudes toward transsexual men (Transmen-IAT) and transsexual women (Transwomen-IAT). A sample of 344 Mechanical Turk participants from the United States (173 women, 129 men, 43 transgender) completed the following: GI-IATs, Genderism and Transphobia Scale, Allophilia Toward Transsexual Individuals Scale, Social Desirability Scale-17, feelings thermometers, and ratings of intention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 80 publications
(122 reference statements)
1
17
0
Order By: Relevance
“…More notably, these results differ from previous work assessing implicit transgender attitudes. In Wang-Jones et al (2017), participants classified as transgender ( N = 42) showed no ingroup favoritism on IATs measuring associations toward “transsexual men” (vs. “biological men”) or “transsexual women” (vs. “biological women”). One potential explanation may come from differing methods for classifying transgender participants.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…More notably, these results differ from previous work assessing implicit transgender attitudes. In Wang-Jones et al (2017), participants classified as transgender ( N = 42) showed no ingroup favoritism on IATs measuring associations toward “transsexual men” (vs. “biological men”) or “transsexual women” (vs. “biological women”). One potential explanation may come from differing methods for classifying transgender participants.…”
Section: Discussionmentioning
confidence: 98%
“…In fact, the only existing measure of implicit transgender attitudes (Wang-Jones et al, 2017, 2018) used an Implicit Association Test (IAT; Greenwald et al, 1998), and found that implicit attitudes toward “transsexual men” and “transsexual women” correlate reliably but weakly with parallel explicit attitudes. However, this implicit measure had features that limit its generalizability.…”
Section: The Role Of Implicit Transgender Attitudesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the measure of explicit STEM gender associations used in this study was a 1-item 0-100 feelings thermometer. Although feeling thermometers have been used in the past to successfully measure stereotypes (Wang-Jones et al, 2017), having a scale with multiple items may increase reliability. Finally, the scale order was not randomized, and order effects could not be tested.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…-cf., Johnson, Lakhan, Lecci, Dovidio, & Schellhaas, 2020), or across different gender categories (e.g., do Conservatives become more anti-Trans when frustrated? -cf., Wang-Jones, Alhassoon, Hattrup, Ferdman & Lowman, 2017). The present work constitutes a template for exploring other social biases that may be augmented by arbitrary reward omissions (Amsel, 1992).…”
Section: Discussionmentioning
confidence: 99%